Literary Representation of Women in South Asian Writings - Dhobi, Saleem (Patan Prospective Journal, 2022)
This paper scrutinizes the portrayal of women in South Asian fiction by female writers who have been vocal and have been advocating the rights of women in general and the rights and position of Muslim women in particular. How society treats women at different phases of life: daughterhood, womanhood and motherhood have been the point of examination in this article. The paper employs the radical feminist perspective as a theoretical tool to examining the represented position of women in novels of Monica Ali and Taslima Nasreen who belong to Bangladesh but reside beyond the national territory. Ali’s Brick Lane and Nasreen’s My Girlhood have been undertaken as the primary texts to study about the depiction of Muslim women. Women are not inferior to men in any respect. However, through socialization, they are made to feel that they are subordinates to men and their lives are incomplete without the support of men. This feeling instead of capacitating women weakens their will power and ultimately they develop a psyche that men are superior beings and therefore, they must abide by the dictates of men in both personal and professional lives. Both of the novels portray women as daughters, wives and mothers who subordinate men and stay obedient to their counterparts to the extent they are devoid of their existence. When they realize their subjugated position and know the world around, they seek for their individual identity. Despite such portrayals of women’s subjugation and marginalization in patriarchy fueled by doctrines of Islam, some feminist critics including Hosseini assert that the pathetic condition of women in Muslim societies is because of political Islam. Therefore, the generalized view of Islam is questionable.